2011
DOI: 10.1136/gutjnl-2011-300832
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus strains of subgenotype A2 with an identical sequence spreading rapidly from the capital region to all over Japan in patients with acute hepatitis B

Abstract: Objective To examine recent trends of acute infection with hepatitis B virus (HBV) in Japan by nationwide surveillance and phylogenetic analyses. Methods During 1991 through 2009, a sentinel surveillance was conducted in 28 national hospitals in a prospective cohort study. Genotypes of HBV were determined in 547 patients with acute hepatitis B. Nucleotide sequences in the preS1/S2/S gene of genotype A and B isolates were determined for phylogenetic analyses. Results HBV genotype A was detected in 137 (25% (acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 41 publications
3
44
0
Order By: Relevance
“…In Shanghai, China, where genotypes B and C prevail, a population-based surveillance showed 8.50 % of the adult patients with AHB became chronic; in the 68 AHB patients with genotype data available, the only identified risk factor for chronicity was sub-genotype C2 [31]. In Japan, a large prospective cohort study showed that the proportion of AHB patients with genotype A (particularly sub-genotype A2, mainly through sexual contact) is increasing year by year, with a chronicity rate of 4 % [32]. A nationwide multicenter cohort study in Japan on 212 AHB patients revealed that genotype A was independently associated with viral persistence following AHB [33].…”
Section: Hbv Genotypes and Clinical Manifestation In Asiamentioning
confidence: 97%
“…In Shanghai, China, where genotypes B and C prevail, a population-based surveillance showed 8.50 % of the adult patients with AHB became chronic; in the 68 AHB patients with genotype data available, the only identified risk factor for chronicity was sub-genotype C2 [31]. In Japan, a large prospective cohort study showed that the proportion of AHB patients with genotype A (particularly sub-genotype A2, mainly through sexual contact) is increasing year by year, with a chronicity rate of 4 % [32]. A nationwide multicenter cohort study in Japan on 212 AHB patients revealed that genotype A was independently associated with viral persistence following AHB [33].…”
Section: Hbv Genotypes and Clinical Manifestation In Asiamentioning
confidence: 97%
“…Nosocomial transmission and unsafe injection practices are considered responsible for more than 60% of HBV infections in Central Europe [87] . Though genotype E is transmitted by heterosexual relations in Africa, genotype A and particularly genotype G were isolated from men who have sex with men in Europe and Canada [81,88] . In West Asia and in the Middle East (where genotype D is dominant), the route of transmission and HBV seroprevalence depend on the region.…”
Section: Genotype Epidemiological Distinctionsmentioning
confidence: 99%
“…Some genotypes are more associated with particular kinds of prognoses, such as acute forms of disease [88] . Several reports showed that genotype A evolves more rapidly in patients than genotype D does, which poses problems for treatment [16] .…”
Section: Genotypes' Impact On Clinical Outcomesmentioning
confidence: 99%
“…Although locally circulating HBV strains may be expected to be genetically (20,21). As noted, rapid transmissions among acutely infected MSM in the Netherlands and Japan (25,26) were associated with genetically identical or closely related A2 strains. The data from Japan also indicate a greater propensity of primary infection with A2, compared to other genotypes, associated with persistent HBV infection (29,30).…”
Section: Genetic Analysis Of Hbv Wg Sequences Confirmed Significant Pmentioning
confidence: 99%
“…In Europe, the majority of incident HBV strains belong to A2 (19,20), with specific strains identified in English prisons (21), in outbreaks of nosocomial HBV transmissions in Germany (22) and Belgium (23), and among MSM in The Netherlands (24). In Japan, HBV A2 has been observed to be spreading not only within the MSM community (25) but also from there to the general population (26). The National Heart, Lung, and Blood Institute Retrovirus Epidemiology Donor Study-II (REDS-II) of 34 million U.S. blood donations between 2006 and 2009 reported that the majority of 193 donor HBV strains (37%) consisted of A2, with incident donors carrying higher frequencies of A2 (67%) compared to those in prevalent donors (27%) (27).…”
Section: Hbv Genetic Diversitymentioning
confidence: 99%